Seismic Evaluation of Diagonally Braced Steel-panel Suspended Ceiling System using Shaking Table Tests - Lee, Jae Sub; Jung, Dam I.; Lee, Doo Yong; Cho, Bong Ho (Journal of the Architectural Institute of Korea, 2022)
After the 2016 Kyoung-Ju and 2017 Po-Hang earthquakes, securing seismic performance of non-structural elements as well as structural elements of buildings has become an important design issue in Korea. Suspended ceilings can cause damage to life and property to residents due to the falling of finishing materials or collapse of ceiling frame members during earthquakes, and in particular, it can cause secondary damage by blocking the evacuation route. According to KDS 41 17 00, if the ceiling area of the Seismic design category D building exceeds 250 m², a seismic bracing system must be applied. This paper proposes a rigid bracing system to secure the seismic performance of the steel panel T-bar ceiling system, and evaluates the performance through the shake table test. Through experiments on two ceiling systems with different bracing arrangements, dynamic behaviors such as natural frequencies and relative displacements were analyzed, and the cause of panel separation during earthquakes was found. It was found that the relative displacement between the grid members was the biggest cause of panel detachment of the rigid braced ceiling system. In order to reduce the relative in-plane displacement of the ceiling, a method of narrowing the spacing between the braces or increasing the in-plane rigidity may be used.
Keywords: Non-structural element; Rigid brace; Seismic performance; Shaking table test; Suspended ceiling